Degradation of social institutions and land use: unfolding feedback mechanisms between afforestation with fast-growing species and living conditions in rural areas - Martínez-Cabrera, Helena; Rodríguez- Rodríguez, Gonzalo; M. Ballesteros, Hugo (Revista Galega de Economía, 2020)
Evidence of the irreversibility of certain social changes has been accumulating in recent years, but both the processes by which perceptions of irreversibility are formed and the relationships between those elements that feed them remain largely unexplored. This work deals with the contribution of land uses to the creation of liveable rural areas, one of the main socio-economic challenges to be faced. Interviews with 10 experts were conducted in 2016 to collect perceptions among forest owners. Through a Causal Loop Diagram, a model of perceived well-being is developed capturing present dynamics between social and natural subsystems as well as their possibilities for change. The results confirm that variables such as self-efficacy, sense of place, or sense of control underlie a perception of irreversibility and reduce the scope for collective action. The need to consider the population’s perception in designing effective rural policies is underlined.